Guitar Simulator Based on Realtime Recording - Ragil Bintang Brilyan; Eko Mulyanto Yuniarno; Yoyon Kusnendar Suprapto (Jurnal Teknik ITS, 2021)
Music is an art that combines several compositions of musical instruments. Among them are vocals, piano, guitar, bass, drums, and so on. To play a musical instrument also requires a technique to a formula, so that the music game becomes more harmonious. Techniques and formulas in playing musical instruments include tempo, rhythm, how to play a musical instrument, to chords. But for people who are just learning to play a musical instrument, it is certainly difficult to know the formula for the chords to be played. Not to mention when the sound of the chord being played is different from the sound of the intended chord. This can change a song being played sound fake or deviate from the actual song. Often in learning to play musical instruments, some media do not explain or explain how the chords are played and whether the chords are played correctly. One way to determine the accuracy of the chord sound in a self-taught music game, can be done using the help of Machine Learning. This method records the sound of guitar chords being played and classifies guitar chords according to their original sound. However, chords that can be classified are still limited to basic chords, because they are intended for the most basic learning. And for the display of the chord formula that is played it will be more interactive when using game design.